Cyberviolences de genre. Définir et rendre compte du cybersexisme dans les pratiques numériques adolescentes - Sigolène Couchot-Schiex; Gabrielle Richard
A majority of French high students have a very active online presence. Almost all of them have a smartphone and social network apps are the one they use most of their time. Recent studies have documented the negative interactions occurring in cyberspace, defining them as instances of "cyberviolence". These are highly gendered social relations inasmuch as they encourage conformity to rigid gender norms (in many ways sexist, sexual or homophobic in nature). This paper will document instances of "gendered cyberviolence" as reported by youth from the Île-de-France region who have taken part in a study conducted by the Observatoire Universitaire International Éducation et Prévention (Université Paris-Est Créteil) and sponsored by the Centre Hubertine Auclert. Analyzing both quantitative and qualitative, it will discuss the existence of polymorphous and ordinary instances of cybersexism, targeting both girls and boys whose behaviors or preferences are considered gender atypical. All in all, this paper will relate the genesis of the concept of cybersexism, which the authors suggest may best qualify the episodes of violence that are anchored in a gender-normative order.